New directions in regional economic development : the role of entrepreneurship theory and methods, practice and policy - Desai, Sameeksha (Edward Elgar CheltenhamGB, 2011)
Examines some of the new directions in regional economic development, specifically the perspective that local initiative matters in how a regions grows, adapts to change and adjusts to disequilibrating physical and societal shocks. Notes that there are barriers to entrepreneurial performance that vary from one region to another (and from one nation to another). Proposes the concept of a 'knowledge filter' to offer an explanation for the variation in the rate at which knowledge and knowledge conversion can occur, and likewise variation in the level of entrepreneurial success.